Long-term differential effects of tree species on soil nutrients and fertility improvement in agroforestry parklands of the Sahelian Niger. Issue 4 (2nd October 2019) - B. Diallo, Mariama; Akponikpè, P. B. Irénikatché; Fatondji, Dougbédji; Abasse, Tougiani; Agbossou, Euloge K.
ABSTRACT: Soil sampling was conducted in a semi-arid region of Niger to study the long-term differential impacts of trees and shrubs on soil chemical properties. The sampling considered three factors: species, position to trunk (underneath crown, crown neighborhood, control) and soil horizon depth. Two shrub species ( Annona senegalensis and Combretum aculeatum ), and two tree species ( Faidherbia albida and Piliostigma reticulatum ) were investigated. We analyzed the following soil properties and nutrients: pH, Organic Carbon (OC), Ammonium-N (NH4), Phosphorus (P), Sodium (Na), Potassium (K), Calcium (Ca) and Magnesium (Mg). The results showed that the trees significantly affected each soil property considered, although with different magnitudes according to species. F. albida and P. reticulatum improved soil quality more than the other two species for almost all the investigated soil parameters. The effect of tree/shrub species on soil fertility extended to crown neighborhood. On average, all soil nutrients contents except Mg were consistently higher directly under crown compared to crown neighborhood and control position. We recommend that tree planting or Farmer Managed Natural Regeneration (FMNR) in agroforestry parklands be guided not only by the common objectives of improving soil fertility and producing food and fodder, but also consider the selection of the appropriate tree species.